Effect of Density and Lethargy Duration in Prerelease Packaging of the Fruit Fly (Diptera: Tephritidae) Parasitoid, Diachasmimorpha longicaudata (Hymenoptera: Braconidae). Issue 1 (27th February 2020) - Cancino, Jorge; Leal-Mubarqui, Rubén; Angulo, Roberto; Pérez, Cesar; Tirado, Lucy
Abstract: Different densities prerelease packing and times of lethargy in the fruit fly parasitoids Diachasmimorpha longicaudata (Ashmead) were evaluated in order to standardize the process of chilled insect technique for this species. Adults were kept at densities of 0.048, 0.072, 0.096, 0.120, and 0.144 parasitoids/cm 2 before release in a México tower, where thermal lethargy was induced at a temperature of 2 ± 2°C for 45 min. Samples of parasitoids were collected to evaluate mortality, survival, fecundity, and flight capacity. All densities showed a similar mortality, both for males (ca. >10%) and females (ca. <7). There was no effect of density on survival and flight capacity in both sexes. On the other hand, fecundity increased with density, 1.66 sons/♀/day, similar to the control. We conclude that a density of 30, 000 pupae per cage (0.144 parasitoids/cm 2 ) is adequate for the massive prerelease packaging of the parasitoid D. longicaudata . Regarding the thermal lethargy period, 180 min under 2 ± 2°C conditions, considered as time for management, does not affect the survival, fecundity, and flight capacity of adults. The results obtained are of great utility to establish prerelease packaging parameters for D. longicaudata used in the biological control of Tephritidae fruit fly populations.